Association of PTSD symptom groups with functional impairment and distress in trauma-exposed disaster survivors. Issue 9 (1st July 2020) - North, Carol S.; Van Enkevort, Erin; Hong, Barry A.; Surís, Alina M.
Abstract: Background: In the nearly a quarter of a century since the addition of the clinically significant distress/impairment criterion to the definition of PTSD in DSM-IV, little research has been done to examine the association of this criterion with symptom group criteria and with the numbing subgroup specifically. This study was conducted to examine these relationships in a large database of disaster survivors consistently studied across 12 different incidents of the full range of disaster typology. Methods: Analysis was conducted on a merged database representing 1187 trauma-exposed survivors of 12 different disasters studied systematically. DSM-IV-TR criteria for disaster-related PTSD were assessed with the Diagnostic Interview Schedule. Results: PTSD Group C (avoidance/numbing) and numbing specifically were less common and more associated than other symptom groups with criterion F (distress/impairment). Consistently in multivariable models, group C and numbing were independently associated with criterion F. Group D (hyperarousal) was less strongly associated with criterion F. Neither group B (intrusion) nor avoidance were associated with criterion F. Conclusions: In this and other studies, group C and numbing specifically have been shown to be associated with criterion F, which is consistent with the demonstration that group C and the numbing component specifically are central to the psychopathology of PTSD. The addition of the distress/impairment requirement broadly across the psychiatric diagnoses in DSM-IV added little value to PTSD symptom criteria. Future revisions of diagnostic criteria may benefit by carefully considering these findings to possibly re-include a prominent numbing symptom section.